The many resurrections of Henry Box Brown - Cutter, Martha J. (University of Pennsylvania Press, 2022)
On March 23, 1849, Henry Brown climbed into a large wooden postal crate and was mailed from slavery in Richmond, Virginia, to freedom in Philadelphia, Pennsylvania. "Box Brown," as he came to be known after this astounding feat, went on to carve out a career as an abolitionist speaker, actor, magician, hypnotist, and even faith healer, traveling the United States, the United Kingdom, and Canada until his death in 1897.The Many Resurrections of Henry Box Brown is the first book to show how subversive performances were woven into Brown's entire life, from his early days practicing magic in Virginia while enslaved, to his last shows in Canada and England in the 1890s. It recovers forgotten elements of Brown's history to illustrate the ways he made himself a spectacle on abolitionist lecture circuits via outlandish performances, and then fell off these circuits and went on to reinvent himself again and again. Brown's stunts included creating a moving panoramic picture show about his escape; parading through the streets dressed as a "Savage Indian" or "African Prince"; convincing hypnotized individuals that they were sheep who would gobble down raw cabbage; performing magic, dark séances, and ventriloquism; and even climbing back into his "original" box to jump out of it on stage.In this study, Martha J. Cutter analyzes contemporary resurrections of Brown's persona by leading poets, writers, and visual artists. Both in Brown's time and in ours, stories were created, invented, and embellished about Brown, continuing to recreate his intriguing, albeit fragmentary and elusive, story. The Many Resurrections of Henry Box Brown fosters a new understanding not only of Brown's life but of modern Black performance art that provocatively dramatizes the unfinished work of African American freedom.